AKUISISI SAHAM HUBUNGANNYA DENGAN INVESTASI ASING DIKAITKAN DENGAN UNDANG-UNDANG NOMOR 5 TAHUN 1999 TENTANG LARANGAN PRAKTEK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT - Juli Asril; Imas Rosidawati Wiradirja (Jurnal Media Justitia Nusantara, 2015)
Share acquistion is a very popular formof acquistion carried out in every company takeover. Share acquistion will, however, become an extraordinary matter when it creates monopoly and business competition. Acquistion is therefore still deemed as a controversial decision as it possesses dramatic and complex implications, detrimental as wel as beneficial to manyparties. With respectto the above, this research needed to study : First, what are the legal implications when share acquistion of a national company by a foreign company creates business competitions, and second, what legal protection is there for minoritysharehoders who suffered through the acquistion of a nationalcompany by a foreign company.